2009
DOI: 10.1152/ajpcell.00649.2008
|View full text |Cite
|
Sign up to set email alerts
|

The role of transferrin receptor 1 and 2 in transferrin-bound iron uptake in human hepatoma cells

Abstract: Herbison CE, Thorstensen K, Chua AC, Graham RM, Leedman P, Olynyk JK, Trinder D. The role of transferrin receptor 1 and 2 in transferrin-bound iron uptake in human hepatoma cells. Am J Physiol Cell Physiol 297: C1567-C1575, 2009. First published October 14, 2009; doi:10.1152/ajpcell.00649.2008.-Transferrin receptor (TFR) 1 and 2 are expressed in the liver; TFR1 levels are regulated by cellular iron levels while TFR2 levels are regulated by transferrin saturation. The aims of this study were to 1) determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 45 publications
4
51
0
Order By: Relevance
“…In support of this, we recently observed in hepatoma cells that changes in iron uptake were small when Tfr2 protein expression was modified by diferric transferrin, Tfr2 overexpression, and Tfr2 underexpression using small interfering RNA. 39 In addition, in vivo hepatic iron uptake from plasma transferrin in Tfr2 (Y245X) mutant mice with nonfunctional Tfr2 was only approximately 20% lower than in iron-loaded wild-type mice. 40 This provides further support for a limited role of Tfr2 in liver iron transport and suggests that other transferrinbound iron transport pathways exist.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, we recently observed in hepatoma cells that changes in iron uptake were small when Tfr2 protein expression was modified by diferric transferrin, Tfr2 overexpression, and Tfr2 underexpression using small interfering RNA. 39 In addition, in vivo hepatic iron uptake from plasma transferrin in Tfr2 (Y245X) mutant mice with nonfunctional Tfr2 was only approximately 20% lower than in iron-loaded wild-type mice. 40 This provides further support for a limited role of Tfr2 in liver iron transport and suggests that other transferrinbound iron transport pathways exist.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Herbison et al (36) showed that knockdown of TFR1 in HuH7 cells resulted in 80% less assimilation of iron from 50 nM TF compared with controls. The lower iron levels were due to diminished uptake of TF because TF uptake was also 80% lower.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced iron intake or suppressed iron excretion can be assumed to be responsible for increased iron deposition in the liver. In general, Tfr1 plays an important role in hepatic iron uptake (Herbison et al, 2009), but Tfr2 as well as Tfr1 may have contributed to an increase in hepatic iron levels in experiment 1. In the duodenum, the mRNA levels of DMT1, ferritin H, and hephaestin were more significantly elevated in the CE group than the C group, whereas DMT1 mRNA expression tended to be increased in the HE group compared with the H group.…”
Section: Effects Of Ezetimibe On Iron Metabolismmentioning
confidence: 99%